The role of NETosis in the pathogenesis of immunoinflammatory rheumatic diseases - E. L. Nasonov; A. S. Avdeeva; T. M. Reshetnyak; A. P. Aleksankin; Yu. P. Rubtsov (Научно-практическая ревматология)
Uncontrolled activation of neutrophils is considered an important mechanism of thromboinflammation and fibrosis in immunemediated rheumatic diseases (IMRD), malignant neoplasms, atherosclerosis, COVID-19 and many other acute and chronic inflammatory diseases of humans. Particular attention has been drawn to the ability of neutrophils to form “network” (web-like) structures, called “neutrophil extracellular traps” NETs. The process associated with the formation of NETs and the weakening of their degradation is called “NETosis”. The publication summarizes data on the role of NETosis in the pathogenesis of IMRD and discusses the prospects for pharmacotherapy aimed at preventing the formation and destruction of NETs.